PENGGUNAAN MEDIA INTERAKTIF CANVA DALAM PEMBELAJARAN TIK UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VII DI SMPN 7 KOTA CILEGON - Rokib; Kurniati Rahmadani; Desty Endrawati Subroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Rokib, 2024 The title of this research is the use of interactive media Canva in ICT learning to increase students' learning motivation in class VII at SMP Negeri 7 Cilegon City. This research aims to determine the increase in students' learning motivation towards using Canva interactive learning media in mathematics subjects. This research was conducted in class VII of SMP Negeri 7 Cilegon. This research measures students' learning motivation and students' responses. Data collection uses questionnaires and observations. The results of the research showed that the results of the student motivation questionnaire had an overall average rating of 76% with good criteria and from the interview results, students gave a positive response to Canva interactive learning media of 87.8% in the very good category. These results show that Canva's interactive learning media in software introduction material can be used as a learning medium.